SURVEI KEPUASAN MAHASISWA TERHADAP KINERJA DOSEN MENGAJAR, SARANA/PRASARANA PEMBELAJARAN DAN LAYANAN ADMINISTRASI AKADEMIK - Andriana, Encep; Hidayat, Sholeh; Nulhakim, Lukman (Bestari: Jurnal Pendidikan dan Kebudayaan, 2025)
Abstract: This study aims to evaluate the level of student satisfaction with three main aspects of the educational environment in higher education: lecturer performance in teaching, learning facilities/infrastructure, and academic administration services. This research uses a quantitative approach method with data collection techniques through questionnaire survey instruments specifically designed to measure student perceptions and satisfaction in each aspect studied. The results showed that the level of student satisfaction with the performance of lecturers in teaching was generally high, but there were several indicators that required special attention, such as the provision of learning media in the teaching and learning process. Learning facilities/infrastructure received mixed responses; some facilities are considered adequate, while others still need to be improved, especially in terms of accessibility and comfort. Academic administration services also received an overall positive response, although some aspects, such as service efficiency and responsiveness, still need to be improved.Keywords: Lecturer Performance, Facilities / Infrastructure, Administrative Services, Academic Student Satisfaction Abstrak: Penelitian ini bertujuan untuk mengevaluasi tingkat kepuasan mahasiswa terhadap tiga aspek utama dalam lingkungan pendidikan di perguruan tinggi: kinerja dosen dalam mengajar, sarana/prasarana pembelajaran, dan layanan administrasi akademik. Dalam penelitan ini menggunakan metode pendekatan kuantitatif dengan teknik pengumpulan data melalui instrumen survei kuesioner yang dirancang khusus untuk mengukur persepsi dan kepuasan mahasiswa pada setiap aspek yang diteliti. Hasil penelitian menunjukkan bahwa tingkat kepuasan mahasiswa terhadap kinerja dosen dalam mengajar umumnya tinggi, namun terdapat beberapa indikator yang memerlukan perhatian khusus, seperti diadakannya media pembelajaran  dalam proses belajar-mengajar. Sarana/prasarana pembelajaran mendapat tanggapan yang beragam; beberapa fasilitas dinilai memadai, sementara yang lain masih perlu ditingkatkan, terutama dalam hal aksesibilitas dan kenyamanan. Layanan administrasi akademik juga mendapatkan tanggapan yang positif secara keseluruhan, meskipun beberapa aspek, seperti efisiensi dan responsivitas layanan, masih perlu ditingkatkan.Kata Kunci: Kinerja Dosen, Sarana/Prasarana, Layanan Administrasi, Akademik Kepuasan Mahasiswa